2022
DOI: 10.3389/fpubh.2022.957547
|View full text |Cite
|
Sign up to set email alerts
|

A general health promotion approach to helping smokers with non-communicable diseases quit smoking: A pilot randomized controlled trial

Abstract: BackgroundDespite evidence showing that continued smoking in patients with non-communicable diseases can reduce treatment efficacy and increase the risk of disease progression and multimorbidity, many smoker patients either have no intention to quit or have had failed attempts at quitting.ObjectiveTo examine the feasibility of a general health promotion approach that uses instant messaging to deliver brief motivational interviewing to help smokers with non-communicable diseases quit smoking.MethodsIn total, 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In our previous study [7], some young smokers expressed their desire to quit smoking because of the need to wear a mask, which made it harder to smoke in public areas; the inability to smoke at home; and a lack of peer pressure to smoke. Second, unlike the majority of young smokers, who tend to be occasional smokers with mild nicotine dependency [29], many adult smokers are chronic smokers with moderate-to-high nicotine dependency [30]. In fact, cigarette smoking is so addictive that many chronic smokers either have no intention of quitting or have difficulty quitting [28].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study [7], some young smokers expressed their desire to quit smoking because of the need to wear a mask, which made it harder to smoke in public areas; the inability to smoke at home; and a lack of peer pressure to smoke. Second, unlike the majority of young smokers, who tend to be occasional smokers with mild nicotine dependency [29], many adult smokers are chronic smokers with moderate-to-high nicotine dependency [30]. In fact, cigarette smoking is so addictive that many chronic smokers either have no intention of quitting or have difficulty quitting [28].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a pilot RCT involving 60 smokers in Hong Kong from 2019 to 2020 found that more than 90% of participants owned a smartphone and could use an instant messaging application (e.g. WhatsApp/WeChat) to communicate [25]. Smokers who do not own a smartphone or are unable to receive WhatsApp/WeChat messages and those with mental illness will receive a smoking cessation leaflet and brief advice on smoking cessation, but will be excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
“…to communicate [25]. Smokers who do not own a smartphone or are unable to receive WhatsApp/WeChat messages and those with mental illness will receive a smoking cessation leaflet and brief advice on smoking cessation, but will be excluded from the study.…”
Section: Ethicsmentioning
confidence: 99%